Ergonomic solution for working at desks - Lim, Joshua Matthew Tze Han (Nanyang Technological University, 2022)
At the start of this project, an analysis of the existing ergonomic products was conducted. It was determined that the products were lacking and something new could be created. A new idea of dynamic ergonomics was conceptualised. Despite adopting an ergonomic position, people were still feeling body strains and it was because they had a stationary posture for long durations at a time. An automated desk riser was proposed to keep users healthy and energised even through hours of prolonged use. It can make minute positional adjustments over the course of the day to induce natural posture changes in the user. This report describes the thought process behind the project, the challenges faced, the decisions made and the effectiveness of the solution.